2013
DOI: 10.4314/ahs.v13i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C and blood transfusion among children attending the Sickle Cell Clinic at Mulago Hospital, Uganda

Abstract: Background: Hepatitis C virus (HCV) accounts for 90% of post-transfusion hepatitis. In Uganda, there has been limited research of prevalence of HCV among sickle cell anaemia (SS) patients, a group at risk for multiple transfusions. Objectives: To establish prevalence of HCV infection and determine whether blood transfusion increases risk among SS patients. Methods 244 SS patients aged 1-18 years were recruited by consecutive sampling. Socio-demographic, clinical and transfusion history was collected. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…11,16 Out of 32 sickle cell patients registered in our study, 8.57% (3/35) were found positive for HCV antibodies. This result is different from that of Moussa et al 9 who detected a prevalence of 23% among 70 Egyptian children with sickle cell disease (SCD) in Egypt and from that of Namasopo et al 10 who reported a prevalence of 2.5% obtained in 244 children in Uganda. The high rate of the HCV antibodies obtained among these high-risk patients can be explained by multiple blood transfusions received, as all the patients were sickle cell anemia-HbSS.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…11,16 Out of 32 sickle cell patients registered in our study, 8.57% (3/35) were found positive for HCV antibodies. This result is different from that of Moussa et al 9 who detected a prevalence of 23% among 70 Egyptian children with sickle cell disease (SCD) in Egypt and from that of Namasopo et al 10 who reported a prevalence of 2.5% obtained in 244 children in Uganda. The high rate of the HCV antibodies obtained among these high-risk patients can be explained by multiple blood transfusions received, as all the patients were sickle cell anemia-HbSS.…”
Section: Discussioncontrasting
confidence: 71%
“…A prevalence of HCV infection varying between 1.25 to 33.5% among these patients has been reported in other parts of the world. 6,9,10 The aim of our study was to determine the seroprevalence of HCV in individuals at risk, namely haemodialysis patients, sickle cell patients at the Yaounde University Teaching Hospital and blood donors in Cameroon.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted on sickle cell patients in Uganda found HCV prevalence to be high among those receiving blood transfusion. 11 Blood transfusion is considered as a major contributing factor for transmission of Hepatitis C. This study concluded by saying that blood components prior to transfusion must be screened for Hepatitis C and transfusion dependent patients must also be screened for Hepatitis C.…”
Section: Comparison Of Sero-positivity Among Male and Female Donorsmentioning
confidence: 96%
“…Hepatitis C virus 2,11 Klebsiella pneumoniae 29 Hepatitis D virus 12 Propionibacterium acnes 3 Hepatitis E virus 13 Pseudomonas species 3,30 Hepatitis G virus 14 Rickettsia rickettsii 31 Human herpesvirus 8 15 Serratia liquefaciens 32…”
Section: Cytomegalovirusmentioning
confidence: 99%